Early predictors of colectomy and long‐term maintenance of remission in ulcerative colitis patients treated using anti‐tumour necrosis factor therapy. Issue 5 (May 2014) - Subramaniam, K.; Richardson, A.; Dodd, J.; Platten, J.; Shadbolt, B.; Pavli, P.
Abstract Background Anti‐tumour necrosis factor (TNF) agents are used as induction and maintenance therapy in ulcerative colitis (UC) refractory to standard therapy and as rescue therapy in acute severe UC (ASUC). Aims To determine long‐term outcomes including colectomy rates, predictors of maintenance of response and remission, risk of serious adverse events by reviewing 12‐year clinical experience from a single centre in Australia. Methods Seventy‐one patients with moderate‐severe UC (Mayo score ≥6) (n = 52) and ASUC (n = 19) treated with anti‐TNF agents were included. Primary end‐points were colectomy at 12 weeks and colectomy‐free survival at last follow up. Secondary endpoints included clinical response (decrease in Mayo score of ≥3) and remission (Mayo score ≤2). Results Colectomy at 12 weeks was 1%, and colectomy‐free survival was 69%. Using full Mayo score, at 3 months, 32/37 (87%) refractory and 9/12 (75%) ASUC patients responded to anti‐TNF therapy; 19/37 (51%) refractory and 8/12 (67%) ASUC patients were in remission. Long‐term response rates (mean follow up 37.4 months) were 24/44 (55%) and 11/15 (73%) in refractory and ASUC groups respectively. Long‐term remission rates were 43% in refractory and 60% in ASUC patients. Twenty two of 71 (31%) underwent colectomy (mean time 50.4 months). Clinical non‐response at 3 months was a predictor of colectomy (hazard ratio = 9.346; P = 0.001). ASUC predicted long‐term maintenance of response (odds ratio 19.4; P = 0.013) and remission (odds ratio 6.13; P = 0.037). Two of 71 patients had serious infections. Conclusions Anti‐TNF therapy is effective in both refractory and ASUC. We argue that early anti‐TNF therapy may improve outcome in UC.